Selenium Inhibitor Coating on NiTi Shape Memory Alloys by Using Thermal Evaporation System - Kok, Mediha; Kanca, Muhammed Sait; Say, Yakup; Saydam, Sinan; Dagdelen, Fethi; Qader, Ibrahim Nazem (Amer Soc Testing Materials, 2024)
NiTi-based memory alloys are often used as intracorporeal implant materials because of their superelasticity and shape memory properties. However, over time, the release of nickel from the NiTi alloy into the body becomes unfavorable; therefore, studies should be conducted to reduce the negative impact of nickel leakage. In this study, the biocompatible selenium element was used to coat NiTi alloys with different thicknesses. The coating process was performed using the thermal evaporation technique. Scanning electron microscopy -Energy Dispersive X-ray Analysis measurements revealed that the surfaces of the samples were well covered. Also, the atomic force microscope device determined the surface roughness of the alloys. The roughness of the surface increased after the coating process. The Tafel test was accomplished to determine the biocompatibility of the coated and uncoated alloys in an artificial body fluid. The corrosion test reveals that Se -coated NiTi alloys have high corrosion resistance.
Keywords: selenium; coating; thermal evaporation system; corrosion; roughness